Developing a Master's Student's Research and Practitioner Skills Through Collaboration With a Doctoral Researcher. Issue 1 (2nd January 2016) - Abrams, Rachel; Nolan, Emily
Abstract: Art therapy master's programs are required to include research coursework in their curriculum; however, they differ in content and types of required projects. Students encouraged to conduct studies that increase the evidence base of art therapy may struggle to do so. This article describes a research collaboration that allowed a master's level student to develop research competency while simultaneously developing her professional identity and clinical skills. A master's level action research study was nested within a doctoral student's larger-scale participatory action research project, which provided a developmentally effective model for achieving mutual goals. As a result, the master's student grew more self-confident in both art therapy and research practice.